Impact of the degree of worsening renal function and B-type natriuretic peptide on the prognosis of patients with acute heart failure - Zhao, Dongfang; Gu, Lijie; Wei, Wenqian; Peng, Dan; Yang, Man; Yuan, Weijie; Rong, Shu (Frontiers in Cardiovascular Medicine, 2023)
Background: The impact of the degree of worsening renal function (WRF) and B-type natriuretic peptide (BNP) on the prognosis of patients with acute heart failure (AHF) is still debatable. The present study investigated the influence of different degrees of WRF and BNP levels at discharge on 1-year all-cause mortality in AHF. Methods: Hospitalized AHF patients diagnosed with acute new-onset/worsening of chronic heart failure (HF) between January 2015 and December 2019 were included in this study. Patients were assigned into high and low BNP groups based on the median BNP level at discharge (464 pg/ml). According to serum creatinine (Scr) levels, WRF was divided into non-severe WRF (nsWRF) (Scr increased ≥0.3 mg/dL and <0.5 mg/dL) and severe WRF (sWRF) (Scr increased ≥0.5 mg/dL); non-WRF (nWRF) was defined as Scr increased of <0.3 mg/dL). Multivariable cox regression was used to evaluate the association of low BNP value and different degrees of WRF with a all-cause death, as well as testing for an interaction between the two. Results: Among 440 patients in the high BNP group, there was a significant difference in WRF on mortality (nWRF vs. nsWRF vs. sWRF: 22% vs. 23.8% vs. 58.8%, P＜0.001). Yet, mortality did not significantly differ across the WRF subgroups in the low BNP group (nWRF vs. nsWRF vs. sWRF: 9.1% vs. 6.1% vs. 15.2%, P=0.489). In multivariate Cox regression analysis, low BNP group at discharge (HR, 0.265; 95%CI, 0.162-0.434; P<0.001) and sWRF (HR, 2.838; 95%CI, 1.756-4.589; P<0.001) were independent predictors of 1-year mortality in AHF.There was a significant interaction between low BNP group and sWRF(HR, 0.225; 95%CI, 0.055-0.918; P<0.05). Conclusions: nsWRF does not increase the 1-year mortality in AHF patients, whereas sWRF does. A low BNP value at discharge is associated with better long-term outcomes and mitigates the adverse effects of sWRF on prognosis.